Healthy Eating: Scrambling for a Variety of Foods - Linda B. Bobroff (EDIS)
Unscramble the words to spell some of the foods that are wise choices for good health. Then write down each of the numbered letters on the blanks below to figure out the message. This revised 1-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, January 2012.